PENERAPAN PENGELOLAAN PEMBELAJARAN MELALUI STRATEGI PQ4R DALAM MENINGKATKAN PEMAHAMAN MATEMATIS SISWA - Asep Rohman; Arvin Efriani; Ambarsari Kusuma Wardani; Husnah Lutfiah (LPPM Universitas Bina Bangsa, 2023)
This study aims to see the management of PQ4R learning in improving students' mathematical understanding. This research is an experimental study. The population in this study was grade VIII MTs Negeri 2 Way Kanan students, the sample in this study was taken by random class technique, by lottery which aimed to take samples that had the same ability so that 37 students of grade VIII A were obtained as an experimental class using the PQ4R strategy and class VIII B totaling 39 students as a control class using expository strategies. After learning in the experimental class and control class for five meetings, continued with data collection. In the data collection process, the author uses tests, documentation and data analysis consisting of pretest and posttest. The research method used to see the magnitude of the influence, data analysis is calculated using the normalized gain formula (N-Gain) then to see the magnitude of the influence a t-test is carried out. The results showed that the average N-Gain obtained by the experimental class was 0.61 while the average gain of the control class was 0.54. Based on the results of analysis and data processing using the t-test, tcount = 2.633 > ttable = 1.992, with a significant level of 5%. Since t counts > ttable then Ho is rejected. Based on these results, it can be concluded that the PQ4R strategy has a significant influence in improving the mathematical understanding of grade VIII MTs Negeri 2 Way Kanan students